Victorian Studies and its Publics - Christ, Carol (Romanticism and Victorianism on the Net, 2009)
AbstractIn reflecting on Victorian studies and its publics, we must remember the peculiar history of the term Victorian—a historical characterization that emerged even while the queen still reigned, a derisive caricature on the part of early twentieth-century writers, and an academic definition of a field of study. Because the Victorians were the first to experience many of the changes fundamental to modern society, Victorian studies has a particular resonance for its many publics.